Hubungan antara faktor-faktor kepribadian dengan stres pada anak-anak usia prasekolah = Relationships between Personality Factors to the Stress of Preschoolers Ages - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Stress could be experienced by everyone both adult and children. Wolman (1972) found that children were more sensitive than adult in responding to stress. This study has two purposes, first is to find out the relationship between age, social maturity, emotional maturity, and anxiety with stress in preschool children, and second is to find out to differences of stress effects in boys and girls. Subjects in this research were 86 children, consisted of 36 boys and 60 girls. All of them were taken from nursery school at Yogyakarta. From the analyses, the results of the study were followed- (1) there was no correlation between age and stress